2023
DOI: 10.3390/nano13071219
|View full text |Cite
|
Sign up to set email alerts
|

Developing Mg-Gd-Dy-Ag-Zn-Zr Alloy with High Strength via Nano-Precipitation

Abstract: A high-performance Mg-10Gd-4Dy-1.5Ag-1Zn-0.5Zr (wt.%, EQ142X) alloy was designed by multi-element composite addition in this work, obtaining a high yield strength (~396 MPa) and ultimate tensile strength (~451 MPa) after hot extrusion and ageing. The high strength is mainly related to fine grains and nano-precipitates, especially the latter. β′ and γ″ nano-precipitation with high fractions are the main strengthening phases, leading to a strengthening increment of ~277 MPa. Moreover, the multi-element alloying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Accordingly, prior research has suggested that introducing nanodeposit networks into fine structures is an effective strategy for developing high-strength Mg alloys. In this research, high-strength Mg alloys, high hardness, etc., can be realized [28]. Another previous study investigated plant-derived exosome-like nanoparticles (PDENs) that consist of a variety of bioactive biomolecules.…”
Section: Nanoparticlesmentioning
confidence: 99%
“…Accordingly, prior research has suggested that introducing nanodeposit networks into fine structures is an effective strategy for developing high-strength Mg alloys. In this research, high-strength Mg alloys, high hardness, etc., can be realized [28]. Another previous study investigated plant-derived exosome-like nanoparticles (PDENs) that consist of a variety of bioactive biomolecules.…”
Section: Nanoparticlesmentioning
confidence: 99%
“…This requires a layer of organic coating on the surface to prevent corrosion and improve its utilization. However, considering that it is not easy to dispose of the coating after the application or recycling of magnesium alloys, it is necessary to consider more environmentally friendly, highly efficient and long-lasting corrosion-resistant coatings [20][21][22][23][24]. In this context, coatings with self-repairing abilities and added microcapsules have emerged.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, nanoparticles have attracted extensive attention in the fields of material chemistry, biopharmaceuticals and environmental science because of their remarkable advantages in biocompatibility and environmental friendliness [16][17][18][19]. Especially, nano-SiO 2 , nano-TiO 2 , nano-ZnO and nano-ZrO 2 have been applied to the corrosion and protection technology of alloy surfaces [20][21][22][23]. This is because the nanoparticles can play a very good role in the process of coating preparation and significantly improve the microstructure of the coating [24,25].…”
Section: Introductionmentioning
confidence: 99%